Quantitative Assessment of Essential and Trace Elements in the Traditional Medicinal Plant Gentiana Chirayita using ICP-MS (International Journal of Food and Nutritional Sciences, 2023)
The method of inductively coupled plasma mass spectrometry (ICP-MS) was used to measurethe amounts of micro and macro elements in the medicinal herb Gentiana Chirayita, which iscommonly used in traditional medicine.